Oxidative stress, lipid peroxidation indexes and antioxidant vitamins in long and middle distance athletes during a sport season - Munoz Marin, D.; Barrientos, G.; Alves, J.; Grijota, F. J.; Robles, M. C.; Maynar, M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The main objective of this study was to observe any changes and possible adaptations produced in MDA and antioxidants vitamins on plasma and erythrocytes in endurance male athletes among an athletic season (12 months). METHODS: Twenty three long and middle distance male athletes participated in this study. Basal MDA on plasma and antioxidant vitamins in plasma and erythrocytes were measured at four moments along the season (0, 3, 6 and 9 months). Fatty acid concentrations in erythrocytes were obtained to determine lipid peroxidation indexes. RESULTS: In plasma, vitamin C suffered significant decreases at 3 and 6 months compared with the begin (P<0.01), and an increase at 9 months, compared with 3 months. On the other hand, vitamin A level was significantly lower at 9 months compared with the other periods (P<0.01 compared with 0 and 6 months; P<0.05 compared with 3 months). In erythrocytes, significant decreases were observed in vitamin E among the season at 6 months and an increase from 6 to 9 months (P<0.05). Vitamin A suffers a significant decrease in both for competitive periods, at 3 and 9 months, compared with the beginning of the season. The most of changes in lipid peroxidation indexes were produced along the firsts 3 months. CONCLUSIONS: 1) Physical training improves the antioxidant systems in order to reduce lipid peroxidation in trained athletes along the season; 2) PUFA/SFA ratios seem more reliable than MDA to observe oxidative stress.